Trastuzumab in the treatment of elderly patients with early breast cancer: Results from an observational study in Germany. Issue 6 (November 2015) - Dall, Peter; Lenzen, Gertrud; Göhler, Thomas; Lerchenmüller, Christian; Feisel-Schwickardi, Gabriele; Koch, Thorsten; Eggert, Jochen; Heilmann, Volker; Schindler, Christof; Wilke, Jochen; Tesch, Hans; Selbach, Johannes; et al.
Abstract: Background: In elderly patients with HER2-positive breast cancer, few data on efficacy and toxicity of adjuvant trastuzumab treatment exists since older patients were in general excluded from large randomized studies. This prospective observational study aimed to confirm the beneficial findings from pivotal trials in age cohorts ≥ 65 years. Materials and Methods: There were no restrictions for recruitment with respect to age or concomitant/sequential adjuvant medication. Long-term relapse/survival status of the patients was assessed once a year. Results: Among the 3940 evaluable patients enrolled between 2006 and 2012 at 339 institutions, 507 were aged between 65 and 69 years, with another 507 patients ≥ 70 years. Elderly patients suffered from significantly more advanced primary tumors. Preceding or concomitant chemotherapy showed decreasing aggressiveness with patient's age. Trastuzumab treatment was stopped prematurely in only 11% of the elderly, but more often than in younger patients ( p  = 0.0008). With 453 events hitherto reported, elderly patients did not exhibit an inferior relapse-free survival when adjusted for other relevant prognostic factors (hazard ratio: 1.01 per year; p  = 0.24). Three-year overall survival was significantly lower in the population older than 64 years than in younger patients (94.2% vs. 96.8%, p  = 0.0011). Conclusions: To our knowledge, our population of elderly patients treated with adjuvant trastuzumab is the largest analyzed so far. The beneficial long-term results were comparable to those in the younger cohorts. Although the risk of cardiotoxicity increased significantly with age, it also remained manageable in older patients. Thus, chronological age alone should not preclude HER2 antibody treatment.